Breaking boundaries : the science of our planet - Rockström, Johan, ....-; Gaffney, Owen, ....-; Thunberg, Greta, 2003- (New York, NY : DK, a division of Penguin Random House LLC, 2021)
Advisors who guided David Attenborough's Our Planet now reveal the full scale of the climate emergency we face, along with the positive message that if we act, we can stabilize Earth's life-support system.
Includes bibliographical references and index.
Keywords: Climate change; Nature